Occupational Stress: The Role of Psychological Resilience in the Ecological Transactional Model - Sivam, Ruben-Wen; Chang, Weining C. (European Scientific Journal, ESJ, 2016)
The present study adopts an ecological approach to examining occupational stress, which incorporates both a trait and a transactional perspective to offer a more comprehensive conceptualization of the antecedents and outcomes of stress with psychological stress as a moderator. Data collected from 182 job incumbents supported the hypothesized relationships among primary appraisal, secondary appraisal, psychological resilience, and maladaptive outcomes. Results from structural equation modeling revealed that primary appraisal affected secondary appraisal, and secondary appraisal, in turn, contributed to maladaptive outcomes. In addition, the relationship between primary appraisal and maladaptive outcomes was partially mediated by secondary appraisal. Consistent with our hypothesis that resilience plays an adaptive role in the stress process, the results indicated that resilience had a direct influence on secondary appraisal. Resilience also affected maladaptive outcomes of stress but this relationship was partially mediated by secondary appraisal.